Compressive Strength Development of Dune Sand Reactive Powder Concrete (RPC) Under Different Curing Conditions - Sara, Ahmed; Farid, Abed; Mohammad, Abdul Mannan (IOP Publishing, 2022)
Reactive powder concrete (RPC) is a special type of concrete with remarkable properties, particularly compressive strength. Some of its main disadvantages include its high cement and SF content, fine quartz with a preferred size of 150 µm - 600 µm, and low water-tobinder ratio. These characteristics increase the cost of RPC production and affect sustainable development. Because of this, researchers have resorted to exploring substitutes to cement and quartz to produce an eco-friendlier type of RPC. Accordingly, this research aims to study the compressive strength development of RPC prepared with dune sand and supplementary cementitious materials (SCM). Three main factors were investigated including 1) replacing cement with 30% ground granulated blast furnace slag (GGBS), 2) using ternary blends of GGBS and fly ash (FA) in RPC, and 3) applying 100ᵒC hot air curing (HAC) to RPC. Overall, the results showed that the compressive strength of HAC and water cured specimens exceeded 120 MPa after 12 hours and 28 days, respectively. Moreover, the compressive strength development of the mixes incorporating SCM was slower than that of the control mix incorporating cement only under HAC conditions.